Analysis and characterization of antiviral drug-resistant cytomegalovirus isolates from solid organ transplant recipients - Lurain, Nell S; Bhorade, Sangeeta M; Pursell, Kenneth J; Avery, Robin K; Yeldandi, Vijay V; Isada, Carlos M; Robert, Emmanuel S; Kohn, Debra J; Arens, Max Q; Garrity, Edward R; Taege, Alan J; Mullen, Martin G; et al. (The Journal of infectious diseases, 2002)
The development of cytomegalovirus (CMV) disease and subsequent emergence of drug-resistant strains was examined in a large group of solid organ transplant recipients; drug-resistant CMV was detected in a total of 30 transplant recipients (20 lung, 5 kidney, 4 heart, and 1 liver). Drug resistance was confirmed both phenotypically and genotypically. The sequences of drug-resistant CMV strains from the same patient differed from drug-susceptible baseline sequences only at single sites previously confirmed to confer drug resistance. At least 1 isolate from each patient had a mutation in the UL97 phosphotransferase coding sequence. Mutations in the DNA polymerase gene were found in 6 of 38 sequenced strains. Lung transplant recipients had the highest incidence of drug-resistant virus: of the 30 patients, 28 were CMV-seronegative transplant recipients of CMV-seropositive organs, which strongly supports the premise that drug resistance is most prevalent in that transplant population.